Prevalence of edentulism in older adults in Latin America. Literature review. - Vizcaíno, Karla (2022)
Edentulism is the partial or total loss of teeth. This has been considered a disability, linked to the quality of life and the economic aspect. In order to know the prevalence of edentulism in older adults in Latin America, this descriptive research was carried out, type bibliographic review.Information was collected from 17 cross-sectional investigations from 10 Latin American countries, in specialized databases such as Lilacs, Scielo, Pubmed, Elsevier and academic Google; in which the prevalence of edentulism is described; that, although it is not a phenomenon exclusive to the geriatric population, it has a high prevalence in this population sector in Latin America. This evidences the need to increase access to oral health services in the region from early ages of life.